Storynomics Bermuatan Narasi Puitik-Ekologis pada Lokapasar Zaskia Mecca - Elvira Damayanti,; Ambarwati, Ari; Alvin Rizqy Al Qodim, (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
Storynomics, poetic narratives, and local ecology can be collaborated to support the creative economy sector with different and more inherent values. This study aims to dissect ecologically charged poetic narratives in storynomics in the Zaskia Mecca (ZM) marketplace. The data in this study are poetic narratives in the data source in the form of product descriptions of the ZM brand on the Shopee Indonesia marketplace. Data were collected using reading and note-taking techniques. Data findings were analyzed using content analysis. The results show that the unique ecology of the archipelago utilized in the poetic narrative is the landscape of the Maluku Islands, Labuan Bajo, Belitung Geopark, Mentawai, Kelimutu, Derawan, Palembang, and Bogor. The typical flora of the archipelago that appears are sandalwood, tuberose, kadupul, and Rafflesia Arnoldii. Through this study, it is hoped that other brands will take similar steps to encourage a more valuable creative economy movement while preserving ecological insights.